Cephalic vein: Saviour in the microsurgical reconstruction of breast and head and neck cancers - Shankhdhar, Vinay K. (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: Reconstruction with microvascular free flaps is considered the reconstructive option of choice in cancer of the head and neck regions and breast. Rarely, there is paucity of vessels, especially the veins, at the recipient site. The cephalic vein with its good caliber and constant anatomy is a reliable recipient vein available in such situations. MATERIALS AND METHODS: It is a retrospective study from January 2010 to July 2012 and includes 26 patients in whom cephalic vein was used for free-flap reconstruction in head and neck (3 cases) and breast cancers (23 cases). RESULTS: All flaps in which cephalic vein was used survived completely. CONCLUSION: Cephalic vein can be considered as a reliable source of venous drainage when there is a non-availability/unusable of veins during free-flap reconstruction in the head and neck region and breast and also when additional source of venous drainage is required in these cases.